PENERAPAN KONSEP MAQASHID ASY-SYARI’AH MENURUT IMAM AL-GHAZALI DAN IMAM ASY-SYATHIBI DALAM INFERENSI HUKUM ISLAM KONTEMPORER: Penerapan Konsep Maqāshid al-Syarī’ah menurut Imam al-Ghazali dan Imam al-Syathibi dalam Inferensi Hukum Islam Kontemporer - Muhammad Faishal Fadhli (Journal of Islamic and Occidental Studies, 2023)
This article aims to apply the concept of maqāsid syarī'ah in contemporary Islamic legal inference. The current problem faced by Muslim is that maqāshid is used to liberalize Islamic law, such as abolishing the obligation to wear the headscarf (hijab), praying in two languages, distribution of inheritance rights for women is greater than for men, and so on, as long as the goals of the law can be achieved. This article is qualitative used library research for data collection from books, journal articles, and documents related to the application of the concept of maqāshid al-syarī'ah according to Imam al-Ghazali and Imam al-Syathibi in contemporary Islamic legal inferences. The collected data were then analyzed using descriptive analysis methods. This study found that the application of maqāshid al-syarī'ah besides having to look at the benefits must also protect the shari'a itself, not violating or deconstructing it.